A reduction-based proof for authentication and session key security in three-party Kerberos. (8th May 2023) - Schwenk, Jörg; Stebila, Douglas
The Kerberos network security protocol provides authentication between clients and servers with the assistance of trusted servers and remains widely used. We give a reduction-based security showing that the mandatory three-party mode of Kerberos authentication and key establishment is a secure authentication protocol under standard assumptions on its encryption scheme; our results can be lifted to apply to quantum adversaries as well. As for many other real-world key exchange protocols, session key indistinguishability cannot be proven for Kerberos since the session key is used in the protocol itself, breaking indistinguishability. We can however show that Kerberos' optional sub-session mode yields secure session keys, and that the hash of the main session key is secure in Krawczyk's generalization of the authenticated and confidential channel establishment model.